Permeation through phospholipid bilayers, skin-cell penetration, plasma stability, and CD spectra of α- and β-oligoproline derivatives - Kolesinska, Beata; Podwysocka, Dominika J.; Rueping, Magnus A.; Seebach, Dieter; Kamena, Faustin; Walde, Peter; Sauer, Markus; Windschiegl, Barbara; Meyer‐Ács, Mira; Vor der Brüggen, Marc; Giehring, Sebastian (Chemistry & biodiversity, 2013)
After a survey of the special role, which the amino acid proline plays in the chemistry of life, the cell-penetrating properties of polycationic proline-containing peptides are discussed, and the widely unknown discovery by the Giralt group (J. Am. Chem. Soc. 2002, 124, 8876) is acknowledged, according to which fluorescein-labeled tetradecaproline is slowly taken up by rat kidney cells (NRK-49F). Here, we describe details of our previously mentioned (Chem. Biodiversity 2004, 1, 1111) observation that a hexa-β3-Pro derivative penetrates fibroblast cells, and we present the results of an extensive investigation of oligo-L- and oligo-D-α-prolines, as well as of oligo-β2h- and oligo-β3h-prolines without and with fluorescence labels (1-8; Fig. 1). Permeation through protein-free phospholipid bilayers is detected with the nanoFAST biochip technology (Figs. 2-4). This methodology is applied for the first time for quantitative determination of translocation rates of cell-penetrating peptides (CPPs) across lipid bilayers. Cell penetration is observed with mouse (3T3) and human foreskin fibroblasts (HFF; Figs. 5 and 6-8, resp.). The stabilities of oligoprolines in heparin-stabilized human plasma increase with decreasing chain lengths (Figs. 9-11). Time- and solvent-dependent CD spectra of most of the oligoprolines (Figs. 13 and 14) show changes that may be interpreted as arising from aggregation, and broadening of the NMR signals with time confirms this assumption.
Gesehen am 25.03.2021